The Impact of University Innovation and Entrepreneurship Education on Entrepreneurial Intention From the Perspective of Educational Psychology - Wang, Qi; Sun, Zhiwei; Wu, Cisheng (Frontiers in Psychology, 2021)
In recent years, innovation and entrepreneurship education is one of the hot spots of higher education research and practice in China. Innovation and entrepreneurship education can be taken as a new direction. Despite the commonly held view that entrepreneurship education drive the promotion of entrepreneurial intention，little is known about the mechanism through which this intervention impacts on entrepreneurial intention。Based on the assimilation learning theory of cognitive structure and the planned behavior theory, the purpose of this work is to analyze the relationship between innovation and?entrepreneurship education (IEE) and entrepreneurial intention from the perspective of educational psychology, to explore the influence mechanism of IEE on entrepreneurial intention, and to promote the success of college students in entrepreneurship. In this study, questionnaires were conducted among college students of different colleges, majors and grades in Anhui province, with the aid of multiple linear regression analysis and mediating effect model analysis. The results show that IEE has positive effect on entrepreneurial intention. In addition, entrepreneurial knowledge plays a mediating role in the relationship between IEE and entrepreneurial intention. And the mediating effect of innovation behavior and entrepreneurial attitude is not obvious. These results are expected to provide evidence for understanding the relationship between IEE and entrepreneurial intention under the background of Chinese education, to enrich and expand the theoretical basis of IEE, and to possess theoretical, empirical and practical significance for the design and implementation of innovation and entrepreneurship education for college students.